Exacerbation of AMD Phenotype in Lasered CNV Murine Model by Dysbiotic Oral Pathogens - Pachiappan Arjunan; Radhika Swaminathan; Jessie Yuan; Mohamed Elashiry; Amany Tawfik; Mohamed Al-Shabrawey; Pamela M. Martin; Thangaraju Muthusamy; Christopher W. Cutler (MDPI AG, 2021)
Emerging evidence underscores an association between age-related macular degeneration (AMD) and periodontal disease (PD), yet the biological basis of this linkage and the specific role of oral dysbiosis caused by PD in AMD pathophysiology remains unclear. Furthermore, a simple reproducible model that emulates characteristics of both AMD and PD has been lacking. Hence, we established a novel AMD+PD murine model to decipher the potential role of oral infection (ligature-enhanced) with the keystone periodontal pathogen Porphyromonas gingivalis, in the progression of neovasculogenesis in a laser-induced choroidal-neovascularization (Li-CNV) mouse retina. By a combination of fundus photography, optical coherence tomography, and fluorescein angiography, we documented inflammatory drusen-like lesions, reduced retinal thickness, and increased vascular leakage in AMD+PD mice retinae. H&E further confirmed a significant reduction of retinal thickness and subretinal drusen-like deposits. Immunofluorescence microscopy revealed significant induction of choroidal/retinal vasculogenesis in AMD+PD mice. qPCR identified increased expression of oxidative-stress, angiogenesis, pro-inflammatory mediators, whereas antioxidants and anti-inflammatory genes in AMD+PD mice retinae were notably decreased. Through qPCR, we detected Pg and its fimbrial 16s-RrNA gene expression in the AMD+PD mice retinae. To sum-up, this is the first in vivo study signifying a role of periodontal infection in augmentation of AMD phenotype, with the aid of a pioneering AMD+PD murine model established in our laboratory.